Positive electrode active material and preparation method and application thereof
By adopting a double-layer clad structure on the lithium-rich manganese-based positive electrode material, the synergistic effect of perovskite material and carbon material/metal carbides is used to solve the problem of irreversible capacity loss and insufficient conductivity during the discharge process, and the overall performance of lithium-ion batteries is significantly improved.
Patent Information
- Application Number
- CN202411919256.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
AI Technical Summary
The lithium-rich manganese-based layered oxide positive electrode material causes incomplete Li+ embedding during the discharge process, resulting in irreversible capacity loss, and poor electronic conductivity, resulting in an increase in the degree of polarization of the battery and a decrease in the dynamic performance.
The positive electrode active material adopts a double-layer cladding structure, the first cladding layer consists of perovskite material, and the second cladding layer consists of carbon material and metal carbides. Through the synergistic effect of this structure and chemical composition, the electronic conductivity and ion conductivity of the material are enhanced.
It effectively reduces irreversible capacity loss, weakens the side reaction between the electrolyte and the active material, reduces the interface impedance, and improves the first-time Coulomb efficiency, rate performance and cycle stability of lithium-ion batteries.
Smart Images

Figure CN119742337A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries and relates to a positive electrode active material, in particular to a positive electrode active material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have attracted great attention due to their high energy density, good safety performance, wide operating temperature range and environmental protection, and are widely used in electronic products, electric vehicles, aerospace and other fields. As one of the important components of lithium-ion batteries, cathode materials have a great influence on the energy density and cycle life of batteries. Among the many cathode materials, lithium-rich manganese-based layered oxides are expected to become one of the most promising cathode materials in the next generation of lithium-ion batteries due to their ultra-high specific capacity, low cost and good safety.
[0003] However, during the discharge process of lithium-rich manganese-based layered oxides, some transition metal ions migrate to the surface oxygen vacancies, which will lead to Li + It cannot be completely embedded in the positive electrode material, resulting in irreversible capacity loss during the first charge and discharge process of the battery; at the same time, the electronic conductivity of this positive electrode material is poor, resulting in an increase in the polarization degree of the battery during the charge and discharge process and a decrease in the electrochemical reaction kinetics of the battery.
[0004] Therefore, improving the lithium-manganese-rich layered oxide positive electrode material is an important means to improve the first coulombic efficiency, rate performance and cycle performance of lithium-manganese-rich positive electrode lithium-ion batteries. Summary of the invention
[0005] In view of the above-mentioned defects, the present invention provides a positive electrode active material having a special double-layer coating structure and chemical composition, which can effectively improve the first coulombic efficiency, rate performance and cycle performance of lithium-ion batteries.
[0006] The present invention also provides a method for preparing the above-mentioned positive electrode active material. The positive electrode active material prepared by the preparation method has a special double-layer coating structure and chemical composition, which can enable the lithium-ion battery to have higher first coulombic efficiency, rate performance and cycle performance.
[0007] The present invention also provides a positive electrode sheet, comprising the positive electrode active material or the positive electrode active material prepared by the preparation method. The positive electrode sheet is used in a lithium-ion battery to effectively improve its first coulombic efficiency, rate performance and cycle performance.
[0008] The present invention also provides a lithium ion battery, comprising the positive electrode active material, or the positive electrode active material prepared by the preparation method, or the positive electrode sheet. The battery has high first coulomb efficiency and rate performance and long cycle life.
[0009] Specifically, the first aspect of the present invention provides a positive electrode active material, the positive electrode active material includes secondary particles formed by agglomeration of primary particles, the secondary particles are provided with a coating layer on the surface, the coating layer includes a first coating layer and a second coating layer; the first coating layer is provided on the surface of the secondary particles, and the second coating layer is provided on the surface of the first coating layer;
[0010] The secondary particles include a lithium-rich manganese-based positive electrode material, the first coating layer includes a perovskite material, the second coating layer includes a carbon material and a metal carbide, and the carbon material includes a one-dimensional carbon material.
[0011] The positive electrode active material as described above, wherein the chemical composition of the perovskite material is A x B 1-x CO3; wherein 0≤x≤1, A and B each independently include at least one of La, Ce, Ca, Sr, Ba, Mg, and Y, and C includes at least one of Al, Ni, Ti, Zr, Cr, Te, and Nb;
[0012] Preferably, the perovskite material includes LaAlO3, La 0.9 Sr 0.1 AlO3, LaNiO3, La 0.9 Sr 0.1 NiO3, BaZrO3, MgTiO3, BaTiO3, SrTiO3, Ba 0.8 Sr 0.2 TiO3、Ba 0.7 Sr 0.3 TiO3、Ba 0.6 Sr 0.4 At least one of TiO3.
[0013] The positive electrode active material as described above, wherein the one-dimensional carbon material comprises at least one of carbon nanotubes, carbon fibers, carbon nanowires, and carbon nanorods;
[0014] And / or, the metal carbide includes at least one of niobium metal carbide, titanium metal carbide, molybdenum metal carbide, and tungsten metal carbide.
[0015] The positive electrode active material as described above, wherein the thickness of the first coating layer is 3 to 7 nm, and / or the thickness of the second coating layer is 5 to 10 nm.
[0016] The positive electrode active material as described above, wherein, further, the mass percentage of the first coating layer in the positive electrode active material is 0.1-2.0wt%, and / or the mass percentage of the second coating layer is 0.5-5.1wt%.
[0017] The positive electrode active material as described above, wherein the mass ratio of the carbon material to the metal carbide is (0.5-50):1.
[0018] The positive electrode active material as described above, wherein the positive electrode active material further comprises a doping element, and the doping element comprises at least one of Ti, Al, Cr, Ta, W, Te, and Nb;
[0019] Preferably, the mass content of the doping element in the positive electrode active material is 1000 to 5000 ppm.
[0020] The positive electrode active material as described above, wherein the carbon material further comprises at least one of graphene, fullerene, Ketjen black, Super-P, and acetylene black.
[0021] The positive electrode active material as described above, wherein the carbon material is graphene and / or Ketjen black.
[0022] The second aspect of the present invention provides a method for preparing the positive electrode active material of the first aspect, comprising the following steps:
[0023] 1) granulating the raw materials including the lithium-rich manganese-based positive electrode material and the perovskite material, and then performing a first sintering in an air atmosphere to obtain a first product; wherein the first sintering temperature is 600 to 800° C., and the holding time is 10 to 15 hours;
[0024] 2) Mixing the raw materials including the first product, the carbon material and the metal carbide with a solvent, evaporating and then performing a second sintering in an inert atmosphere to obtain a positive electrode active material; wherein the second sintering temperature is 300 to 600° C. and the insulation time is 5 to 10 hours.
[0025] The method for preparing the positive electrode active material as described above, wherein step 1) further comprises: mixing and sintering the lithium-rich manganese-based positive electrode material precursor with a lithium source and a compound containing a doping element, the sintering temperature is 800-1000° C., and the holding time is 10-20 hours to obtain the lithium-rich manganese-based positive electrode material; wherein the doping element in the compound containing the doping element comprises at least one of Ti, Al, Cr, Ta, W, Te, and Nb;
[0026] Preferably, the mass ratio of the doping element to the lithium-rich manganese-based positive electrode material precursor is (0.001-0.005):1.
[0027] The method for preparing the positive electrode active material as described above, wherein the mass ratio of the lithium-rich manganese-based positive electrode material to the perovskite material is 1:(0.001-0.02);
[0028] And / or, the mass ratio of the first product to the carbon material and the metal carbide is 1:(0.005-0.05):(0.001-0.01).
[0029] The method for preparing the positive electrode active material as described above, wherein the solvent comprises an anhydrous organic solvent;
[0030] Preferably, the anhydrous organic solvent includes at least one of anhydrous ethanol, o-dichlorobenzene, and N-methylpyrrolidone.
[0031] A third aspect of the present invention provides a positive electrode sheet, comprising the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect.
[0032] A fourth aspect of the present invention provides a lithium-ion battery, comprising the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect, or the positive electrode sheet of the third aspect.
[0033] The positive electrode active material in the present invention includes secondary particles formed by the agglomeration of primary particles. The surface of the secondary particles is coated with a first coating layer, the surface of the first coating layer is coated with a second coating layer, and the first coating layer includes a material with a chemical composition of ABO3, and the second coating layer includes a carbon material (including a one-dimensional carbon material) and a metal carbide. This special coating structure and chemical composition can cooperate with each other and work together, which can not only effectively reduce the irreversible capacity loss of the lithium-rich manganese-based positive electrode material during the discharge process, but also weaken the side reaction between the electrolyte and the active material and reduce the interface impedance; at the same time, it can also effectively improve the overall electronic conductivity and ion conduction of the positive electrode active material, thereby comprehensively improving the first coulombic efficiency, rate performance and cycle stability of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a SEM image of the positive electrode active material prepared in Example 1 of the present invention;
[0035] Figure 2 This is a SEM image of the positive electrode active material prepared in Comparative Example 1 of the present invention;
[0036] Figure 3 This is a TEM image of the positive electrode active material prepared in Example 1 of the present invention;
[0037] Figure 4 This is the XRD diagram of the positive electrode active material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] A first aspect of the present invention provides a positive electrode active material, the positive electrode active material includes secondary particles formed by agglomeration of primary particles, the secondary particles are provided with a coating layer on their surfaces, the coating layer includes a first coating layer and a second coating layer; the first coating layer is provided on the surface of the secondary particles, and the second coating layer is provided on the surface of the first coating layer;
[0040] The secondary particles include a lithium-rich manganese-based positive electrode material, the first coating layer includes a perovskite material, the second coating layer includes a carbon material and a metal carbide, and the carbon material includes a one-dimensional carbon material.
[0041] The inventors of this application have found that the positive electrode active material in the present invention can effectively improve the initial coulombic efficiency, rate performance and cycle performance of the battery. In this regard, the inventors believe that: when the positive electrode active material is in the charging stage, lithium ions are released and part of the lattice oxygen O 2- Due to the oxidation reaction, free oxygen is generated, and the perovskite material in the first coating layer has abundant oxygen vacancies, so it has strong oxygen adsorption and storage capacity, which can control the free oxygen from leaving the system; during the discharge stage, the oxygen adsorbed and stored by the perovskite material is released and embedded in the active material, thereby avoiding the irreversible capacity loss caused by the migration of transition metal ions to the surface oxygen vacancies. However, the ABO3 material has low electronic conductivity, and its coating reduces the electronic conductivity of the active material surface to a certain extent. In this regard, the carbon material and metal carbide in the second coating layer can effectively improve the surface conductivity of the material, improve the polarization effect, and improve the kinetic performance.
[0042] The carbon material in the second coating layer refers to a material with carbon as the main component, and the metal carbide refers to a composite composed of metal elements and carbon elements. Among them, the carbon material includes a one-dimensional carbon material. The one-dimensional carbon material and the metal carbide can cooperate with each other to play a pinning role, inhibiting the volume expansion of the lithium-rich manganese-based positive electrode material caused by the stress generated by phase change during the cycle process, and improving the structural stability of the material; at the same time, the second coating layer formed by the composite of carbon material and metal carbide can be evenly and thinly coated on the surface of the first coating layer, which can not only reduce the capacity loss caused by inactive substances, but also form a complete conductive network, effectively improve the overall conductivity and ion diffusion capacity of the material, reduce the interface impedance, improve the kinetic properties of the positive electrode active material, and avoid the polarization effect caused by excessive local accumulation of ions. At the same time, the double coating layer on the surface of the secondary particles in the positive electrode active material is evenly and firmly coated as a whole, effectively avoiding side reactions between the electrolyte and the active material, and further improving the cycle stability of the battery.
[0043] In summary, using this positive electrode active material in lithium-ion batteries can effectively improve the first coulombic efficiency, rate performance and cycle performance of lithium-ion batteries.
[0044] The lithium-rich manganese-based positive electrode material in the present invention refers to a composite positive electrode material with lithium and manganese as main components, and its general chemical formula is xLi2MnO3·(1-x)LiMO2, wherein 0<x<1, and M is one or more of Ni, Co, and Mn.
[0045] The present invention does not specifically limit the types of carbon materials and metal carbides, and commonly used materials in the art can be selected.
[0046] The present invention does not specifically limit the sources of the lithium-rich manganese-based positive electrode material, carbon material and metal carbide, and any commercially available product or product prepared by a conventional preparation method well known to those skilled in the art may be used.
[0047] In one embodiment, the chemical composition of the perovskite material is A x B 1-x CO3; wherein 0≤x≤1, A and B each independently include at least one of La, Ce, Ca, Sr, Ba, Mg, and Y, and C includes at least one of Al, Ni, Ti, Zr, Cr, Te, and Nb;
[0048] Preferably, the perovskite material includes LaAlO3, La 0.9 Sr 0.1 AlO3, LaNiO3, La 0.9 Sr 0.1 NiO3, BaZrO3, MgTiO3, BaTiO3, SrTiO3, Ba 0.8 Sr 0.2TiO3、Ba 0.7 Sr 0.3 TiO3、Ba 0.6 Sr 0.4 At least one of TiO3.
[0049] When the chemical composition of the perovskite material is A x B 1-x When CO3 further includes the aforementioned specific materials, it can provide more abundant oxygen vacancies, better adsorb and release oxygen, and further reduce irreversible capacity loss.
[0050] When A, B or C includes two or more specific elements, the present invention does not specifically limit the ratio between the specific elements.
[0051] When the perovskite material is a mixture of the aforementioned specific materials, the present invention does not specifically limit the ratio between the specific materials.
[0052] In a specific embodiment, the one-dimensional carbon material includes at least one of carbon nanotubes, carbon fibers, carbon nanowires, and carbon nanorods. When the carbon material is a mixture of the aforementioned multiple substances, the present invention does not specifically limit the ratio between the substances.
[0053] In a specific embodiment, the metal carbide includes at least one of niobium metal carbide, titanium metal carbide, molybdenum metal carbide, and tungsten metal carbide. When the metal carbide is a mixture of the aforementioned multiple substances, the present invention does not specifically limit the ratio between the substances.
[0054] In a specific embodiment, the thickness of the first coating layer is 3 to 7 nm. Within this range, the first coating layer can be evenly coated in the lithium-rich manganese-based positive electrode material, better absorb the oxygen released from the surface of the positive electrode material during charging, further reduce the loss of irreversible capacity, and make the battery have higher first coulomb efficiency and cycle performance. At the same time, it can also avoid the problem of the lithium ion migration path becoming longer due to the excessive thickness of the first coating layer, thereby reducing the lithium ion diffusion capacity.
[0055] Exemplarily, the thickness of the first cladding layer is 3 nm, 4 nm, 5 nm, 6 nm or 7 nm.
[0056] In a specific embodiment, the thickness of the second coating layer is 5 to 10 nm. Since the second coating layer is an inactive substance, the coating thickness of the second coating layer should not be too thick; and in order to ensure the high conductivity of the positive electrode active material, the coating thickness of the second coating layer should not be too thin. Within this range, the thickness of the second coating layer is relatively moderate, which can not only ensure that the positive electrode active material has a high conductivity, but also avoid the capacity loss caused by the inactive substance, so that the lithium-ion battery has a higher rate performance and cycle performance.
[0057] Exemplarily, the thickness of the second cladding layer is 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.
[0058] In a specific embodiment, the mass percentage of the first coating layer in the positive electrode active material is 0.1-2.0wt%. Within this range, the capacity will not be reduced due to excessive coating, while the oxygen adsorption effect of the ABO3 material can be fully utilized, so that the lithium-ion battery has a higher first coulombic efficiency and cycle performance.
[0059] Illustratively, the mass percentage of the first coating layer in the positive electrode active material is 0.1wt%, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2.0wt%.
[0060] In a specific embodiment, the mass percentage of the second coating layer in the positive electrode active material is 0.5-5.1 wt %. Within this range, not only can the positive electrode active material have a high conductivity, but the capacity of the material will not be affected by excessive coating.
[0061] Illustratively, the mass percentage of the second coating layer in the positive electrode active material is 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5.1wt%.
[0062] In a specific embodiment, the mass ratio of the carbon material to the metal carbide is (0.5-50): 1. Within this range, the carbon material and the metal carbide can be better matched, so that the second coating layer is more evenly coated on the surface of the first coating layer, and the second coating layer can also be firmly combined with the first coating layer, thereby further improving the conductivity of the positive electrode active material, and effectively inhibiting the volume expansion of the lithium-rich manganese-based positive electrode material during the cycle process, further improving the cycle performance and rate performance of the battery.
[0063] Illustratively, the mass ratio is 0.5:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1 or 50:1.
[0064] In a specific embodiment, the positive electrode active material further includes a doping element, and the doping element includes at least one of Ti, Al, Cr, Ta, W, Te, and Nb;
[0065] Preferably, the mass content of the doping element in the positive electrode active material is 1000 to 5000 ppm.
[0066] By doping the aforementioned elements into the positive electrode active material, the primary particles can be refined, further shortening the lithium ion transmission path, thereby improving the discharge specific capacity and rate performance.
[0067] When the mass content of the doping element in the positive electrode active material is further within the aforementioned range, the doping element can enter the positive electrode material lattice and will not remain on the material surface due to too high a doping amount, thereby avoiding the generation of impurities on the surface that affect the capacity of the positive electrode active material.
[0068] It should be noted that the above-mentioned doping elements are doped in the bulk phase of the positive electrode active layer material, rather than on the surface.
[0069] When the positive electrode active material is doped with the aforementioned multiple specific elements at the same time, the present invention does not specifically limit the ratio between the specific elements.
[0070] Illustratively, the mass content of the doping element in the positive electrode active material is 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm or 5000 ppm.
[0071] The mass content of the doping element in the positive electrode active material in the present invention can be obtained by inductively coupled plasma emission spectrometry (ICP) testing.
[0072] In a specific embodiment, the carbon material further comprises at least one of graphene, fullerene, Ketjen black, Super-P, and acetylene black; preferably, the carbon material is graphene and / or Ketjen black. In this case, the conductivity of the positive electrode active material can be further improved, so that the battery has a higher rate performance.
[0073] The second aspect of the present invention provides a method for preparing the positive electrode active material of the first aspect, comprising the following steps:
[0074] 1) granulating the raw materials including the lithium-rich manganese-based positive electrode material and the perovskite material, and then performing a first sintering in an air atmosphere to obtain a first product; wherein the first sintering temperature is 600 to 800° C., and the holding time is 10 to 15 hours;
[0075] 2) Mixing the raw materials including the first product, the carbon material and the metal carbide with a solvent, evaporating and then performing a second sintering in an inert atmosphere to obtain a positive electrode active material; wherein the second sintering temperature is 300 to 600° C. and the insulation time is 5 to 10 hours.
[0076] Specifically, in step 1), a granulated product is obtained by granulating a raw material including a lithium-rich manganese-based positive electrode material and a perovskite material, and the granulated product is subjected to a first sintering, the sintering temperature is controlled to be 600-800° C., and the insulation time is 10-15 hours to obtain a first product.
[0077] Exemplarily, the sintering temperature is 600° C., 650° C., 700° C., 750° C. or 800° C.; the sintering temperature is 10 h, 11 h, 12 h, 13 h, 14 h or 15 h.
[0078] The present invention does not specifically limit the granulation method. For example, granulation can be performed by spray drying. Specifically, the raw materials including the lithium-rich manganese-based positive electrode material and the perovskite material are uniformly mixed with deionized water, and granulation is performed by spray drying.
[0079] The present invention does not specifically limit the parameters of spray drying, and conventional parameters in the art may be adopted, such as an inlet temperature of 200-300°C and an outlet temperature of 90-110°C.
[0080] The present invention does not specifically limit the heating rate in the first sintering process. For example, the heating rate is 2 to 5° C. / min.
[0081] The present invention does not specifically limit the ratio of the lithium-rich manganese-based positive electrode material to the perovskite material. Furthermore, by controlling the ratio between the two, the mass percentage of the first coating layer in the positive electrode active material is between 0.1 and 2.0 wt%, and the thickness of the first coating layer is between 3 and 7 nm.
[0082] The perovskite material in the present invention refers to a material having a chemical composition of A x B 1-x CO3 material, wherein 0≤x≤1, A is at least one of La, Ce, Ca, Sr, Ba, Sm, Tm, Y, and B is at least one of Al, Ti, Zr, Cr, Te, Nb.
[0083] The lithium-rich manganese-based positive electrode material in the present invention may be a conventional material in the art, and in one embodiment, may be prepared by the following steps:
[0084] The raw materials including the M source are dissolved in deionized water to prepare a mixed salt solution, which is added to the reactor through a peristaltic pump, and a sodium hydroxide solution is added at the same time. Nitrogen is used as a protective gas, and a hydroxide precursor is obtained through a coprecipitation reaction; the above-mentioned hydroxide precursor is evenly mixed with a lithium source to obtain a mixed material, and the mixed material is heat-sintered at 800-1000° C. for 10-20 hours to obtain a lithium-rich manganese-based positive electrode material.
[0085] Illustratively, the sintering temperature is 800° C., 850° C., 900° C., 950° C. or 1000° C.; and the sintering time is 10 h, 12 h, 14 h, 16 h, 18 h or 20 h.
[0086] The M source in the present invention refers to a raw material containing an M element (Ni, Co, Mn), and the lithium source refers to a raw material containing a lithium element. As long as it contains the target element (Ni, Co, Mn, Li), it belongs to the limitation of the present invention. Exemplarily, the Ni source in the M source includes at least one of nickel sulfate, nickel acetate, nickel nitrate, and nickel formate; the Co source in the M source includes at least one of cobalt sulfate, cobalt acetate, cobalt nitrate, and cobalt formate; the Mn source in the M source includes at least one of manganese sulfate, manganese acetate, manganese nitrate, and manganese formate; the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium chloride, lithium fluoride, lithium sulfate, and lithium nitrate.
[0087] The present invention does not impose any specific limitation on the molar ratio of the elements in the M source. It is only necessary that the chemical composition of the prepared lithium-rich manganese-based positive electrode material satisfies xLi2MnO3·(1-x)LiMO2 (0<x<1); for example, the molar ratio of Ni, Co, and Mn in the M source is (0.2~1):(0~0.5):(0.3~1).
[0088] Furthermore, the concentration of the mixed salt solution is 1-3 mol / L, the concentration of the sodium hydroxide solution is 5-10 mol / L, and the nitrogen inlet flow rate is 2-5 L / min.
[0089] In step 2), the raw materials including the above-mentioned first product, carbon material and metal carbide are added to a solvent, uniformly mixed and then the solvent is evaporated to obtain a dry product, and the dry product is subjected to a second sintering in an inert atmosphere at a sintering temperature of 300 to 600° C. and a holding time of 5 to 10 hours to obtain a positive electrode active material.
[0090] Exemplarily, the sintering temperature is 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C; and the holding time is 5h, 6h, 7h, 8h, 9h or 10h.
[0091] The present invention does not specifically limit the ratio of the mass of the first product to the total mass of the carbon material and the metal carbide. Furthermore, by controlling the ratio between the two, the mass percentage of the second coating layer in the positive electrode active material can be between 0.5 and 5.1 wt%, and the thickness of the second coating layer can be between 5 and 10 nm.
[0092] The present invention does not specifically limit the ratio between the carbon material and the metal carbide. Furthermore, the mass ratio of the carbon material and the metal carbide in the second coating layer can be controlled to be between (0.5-50):1.
[0093] The preparation method of the present invention firstly performs a first sintering of a lithium-rich manganese-based positive electrode material and a perovskite material, wherein the lithium-rich manganese-based positive electrode material includes secondary particles formed by agglomeration of primary particles, and the perovskite material is coated on the surface of the secondary particles to form a first coating layer; then, the first product after the first sintering is mixed with a carbon material and a metal carbide and sintered to obtain a second coating layer coated on the surface of the first coating layer; wherein the first coating layer can adsorb and store oxygen precipitated during the charging process of the positive electrode active material, and embed into the active material during the discharge process, thereby effectively reducing the irreversible capacity loss and improving the first efficiency of the battery; however, the perovskite material will The electronic conductivity of the active material surface is reduced, and the second coating layer can effectively improve the surface conductivity of the material, improve the polarization effect, and improve the kinetic performance; at the same time, the carbon material and metal carbide in the second coating layer can cooperate with each other, which can not only inhibit the volume expansion of the lithium-rich manganese-based positive electrode material during the cycle and improve the structural stability of the material, but also enable the second coating layer to be evenly and thinly coated on the surface of the first coating layer, reduce the capacity loss caused by inactive substances, and form a complete conductive network, thereby improving the overall conductivity and ion diffusion of the material, reducing interface impedance, reducing polarization, and improving rate performance and cycle performance.
[0094] Therefore, the positive electrode active material prepared by the above preparation method can effectively improve the first coulombic efficiency, rate performance and cycle performance of lithium-ion batteries.
[0095] In a specific embodiment, step 1) further comprises mixing and sintering a lithium-rich manganese-based positive electrode material precursor with a lithium source and a compound containing a doping element, the sintering temperature being 800 to 1000° C., and the holding time being 10 to 20 hours, to obtain a lithium-rich manganese-based positive electrode material; wherein the doping element in the compound containing the doping element comprises at least one of Ti, Al, Cr, Ta, W, Te, and Nb;
[0096] Preferably, the mass ratio of the doping element to the lithium-rich manganese-based positive electrode material precursor is (0.001-0.005):1.
[0097] By doping the aforementioned doping elements into the lithium-rich manganese-based positive electrode material, the primary particles can be refined, the lithium ion transmission path can be further shortened, and the battery discharge capacity and rate performance can be improved.
[0098] Furthermore, when the mass ratio of the doping element to the lithium-rich manganese-based positive electrode material precursor is within the aforementioned range, it helps to make the doping element in the finally prepared positive electrode active material between 1000 and 5000 ppm.
[0099] Exemplarily, the mass ratio of the doping element to the lithium-rich manganese-based positive electrode material precursor is 0.001:1, 0.002:1, 0.003:1, 0.004:1 or 0.005:1.
[0100] In a specific embodiment, the mass ratio of the lithium-rich manganese-based positive electrode material to the perovskite material is 1:(0.001-0.02). Within this range, it is helpful to make the mass percentage of the first coating layer in the positive electrode active material between 0.1-2.0wt% and the thickness between 3-7nm, thereby further improving the first coulombic efficiency and cycle performance of the battery and ensuring the rate performance of the battery.
[0101] Exemplarily, the mass ratio of the lithium-rich manganese-based positive electrode material to the perovskite material is 1:0.001, 1:0.01, 1:0.012, 1:0.014, 1:0.016, 1:0.018 or 1:0.02.
[0102] In a specific embodiment, the mass ratio of the first product to the carbon material and the metal carbide is 1: (0.005-0.05): (0.001-0.01). Within this range, it is helpful to make the mass percentage of the second coating layer in the positive electrode active material between 0.5-5.1wt%, the thickness between 5-10nm, and the mass ratio of the carbon material and the metal carbide in the second coating layer between (0.5-50): 1, thereby further improving the first coulombic efficiency, rate performance and cycle performance of the battery.
[0103] Illustratively, the mass ratio of the first product to the carbon material and the metal carbide is 1:0.005:0.05, 1:0.005:0.001, 1:0.05:0.001 or 1:0.05:0.01.
[0104] In a specific embodiment, the solvent includes an anhydrous organic solvent; preferably, the anhydrous organic solvent includes at least one of anhydrous ethanol, o-dichlorobenzene, and N-methylpyrrolidone. When an anhydrous organic solvent is selected as the solvent, the influence of moisture on the positive electrode active material can be avoided.
[0105] The third aspect of the present invention provides a positive electrode sheet, comprising the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect. Therefore, the positive electrode sheet can be used in a lithium-ion battery to effectively improve the first coulombic efficiency, rate performance and cycle performance of the battery.
[0106] The fourth aspect of the present invention provides a lithium-ion battery, comprising the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect, or the positive electrode sheet of the third aspect, so that the lithium-ion battery has a higher first coulombic efficiency and rate performance, and a longer cycle life.
[0107] Hereinafter, the positive electrode active material of the present invention is described in detail through specific examples.
[0108] Example 1
[0109] 1) dissolving nickel sulfate hexahydrate and manganese sulfate monohydrate in a certain molar ratio in deionized water to obtain a mixed salt solution, wherein the molar ratio of nickel to manganese is 35:65, the concentration of the mixed salt solution is 2.5 mol / L, and a 10 mol / L NaOH solution is prepared, and the two are added to a reactor at the same time under the protection of a nitrogen atmosphere, and the temperature of the reaction system is controlled at 60° C. After reaction, aging, washing, filtering, and drying, a hydroxide precursor Ni 0.35 Mn 0.65 (OH)2;
[0110] The hydroxide precursor is mixed with Li2CO3 and Cr2O3 to obtain a mixed material, wherein the ratio of the molar amount of lithium element to the molar amount of metal element in the hydroxide precursor is 1.2:1, and the mass ratio of Cr element to the hydroxide precursor is 0.002:1; the mixed material is placed in a box furnace into which air is passed, and sintered at 900°C for 15 hours to obtain a lithium-rich manganese-based positive electrode material;
[0111] 2) The lithium-rich manganese cathode material and the LaAlO3 material were mixed in a mass ratio of 1:0.001, added to deionized water to obtain a suspension, stirred evenly with a magnetic stirrer, and then spray-dried. The spray-dried product was sintered at 800° C. for 10 h to obtain a first product;
[0112] 3) The first product was mixed with carbon nanotubes and tungsten metal carbide in a mass ratio of 1:0.005:0.001, added to anhydrous ethanol for ultrasonic stirring and dispersion, stirred and evaporated in a 90°C water bath to obtain a dry paste, the paste was dried at 120°C, and the dried product was ground. The ground product was sintered at 300°C in a nitrogen atmosphere for 5 hours to obtain the positive electrode active material of this embodiment; according to ICP testing, the mass content of the doped element in the positive electrode active material was 2000ppm.
[0113] Example 2
[0114] 1) dissolving nickel sulfate hexahydrate, cobalt sulfate heptahydrate and manganese sulfate monohydrate in a certain molar ratio in deionized water to obtain a mixed salt solution, wherein the molar ratio of nickel, cobalt and manganese is 33:1:66, the concentration of the mixed salt solution is 2.5 mol / L, and a 10 mol / L NaOH solution is prepared, and the mixture is added to a reactor at the same time under the protection of a nitrogen atmosphere, and the temperature of the reaction system is controlled at 60° C. After reaction, aging, washing, filtering and drying, a hydroxide precursor Ni 0.33Co 0.01 Mn 0.66 (OH)2;
[0115] The hydroxide precursor is mixed evenly with Li2CO3 and Nb2O5 to obtain a mixed material, wherein the ratio of the molar amount of lithium element to the molar amount of metal element in the hydroxide precursor is 1.5:1, and the mass ratio of Nb element to the hydroxide precursor is 0.001:1; the mixed material is placed in a box furnace into which air is passed, and sintered at 950°C for 10 hours to obtain a lithium-rich manganese-based positive electrode material;
[0116] 2) The lithium-manganese-rich positive electrode material and the SrTiO3 material are mixed in a mass ratio of 1:0.02, added into deionized water to obtain a suspension, stirred evenly with a magnetic stirrer, and then spray-dried. The spray-dried product is sintered at 800° C. for 10 h to obtain a first product;
[0117] 3) The first product was mixed with carbon fiber and molybdenum metal carbide in a mass ratio of 1:0.025:0.005, added to anhydrous ethanol for ultrasonic stirring and dispersion, stirred and evaporated in a 90°C water bath to obtain a dry paste, the paste was dried at 120°C, and the dried product was ground. The ground product was sintered at 300°C in a nitrogen atmosphere for 5 hours to obtain the positive electrode active material of this embodiment; according to ICP testing, the mass content of the doping element in the positive electrode active material was 1000ppm.
[0118] Example 3
[0119] 1) dissolving nickel sulfate hexahydrate and manganese sulfate monohydrate in a certain molar ratio in deionized water to obtain a mixed salt solution, wherein the molar ratio of nickel to manganese is 35:65, the concentration of the mixed salt solution is 2.5 mol / L, and a 10 mol / L NaOH solution is prepared, and the two are added to a reactor at the same time under the protection of a nitrogen atmosphere, and the temperature of the reaction system is controlled at 60° C. After reaction, aging, washing, filtering, and drying, a hydroxide precursor Ni 0.35 Mn 0.65 (OH)2;
[0120] The hydroxide precursor is mixed evenly with Li2CO3 and WO3 to obtain a mixed material, wherein the ratio of the molar amount of lithium element to the molar amount of metal element in the hydroxide precursor is 1.4:1, and the mass ratio of W element to the hydroxide precursor is 0.0025:1; the mixed material is placed in a box furnace into which air is passed, and sintered at 850°C for 20 hours to obtain a lithium-rich manganese-based positive electrode material;
[0121] 2) mixing the lithium-manganese-rich cathode material and the LaNiO3 material in a mass ratio of 1:0.005, adding the mixture into deionized water to obtain a suspension, stirring the mixture evenly with a magnetic stirrer, and spray drying the mixture. The spray-dried product was sintered at 800° C. for 10 h to obtain a first product;
[0122] 3) The first product was mixed with carbon nanowires and titanium carbide in a mass ratio of 1:0.01:0.005, added to anhydrous ethanol for ultrasonic stirring and dispersion, stirred and evaporated in a 90°C water bath to obtain a dry paste, the paste was dried at 120°C, and the dried product was ground. The ground product was sintered at 300°C in a nitrogen atmosphere for 5 hours to obtain the positive electrode active material of this embodiment; according to ICP testing, the mass content of the doping element in the positive electrode active material was 2500ppm.
[0123] Example 4
[0124] 1) dissolving nickel sulfate hexahydrate and manganese sulfate monohydrate in a certain molar ratio in deionized water to obtain a mixed salt solution, wherein the molar ratio of nickel to manganese is 35:65, the concentration of the mixed salt solution is 2.5 mol / L, and a 10 mol / L NaOH solution is prepared, and the two are added to a reactor at the same time under the protection of a nitrogen atmosphere, and the temperature of the reaction system is controlled at 60° C. After reaction, aging, washing, filtering, and drying, a hydroxide precursor Ni 0.35 Mn 0.65 (OH)2;
[0125] The hydroxide precursor is mixed evenly with Li2CO3 and TiO2 to obtain a mixed material, wherein the ratio of the molar amount of lithium element to the molar amount of metal element in the hydroxide precursor is 1.2:1, and the mass ratio of Ti element to the hydroxide precursor is 0.002:1; the mixed material is placed in a box furnace into which air is passed, and sintered at 950°C for 10 hours to obtain a lithium-rich manganese-based positive electrode material;
[0126] 2) The lithium-manganese-rich positive electrode material and the BaTiO3 material are mixed in a mass ratio of 1:0.001, added into deionized water to obtain a suspension, stirred evenly with a magnetic stirrer, and then spray-dried. The spray-dried product is sintered at 700° C. for 10 h to obtain a first product;
[0127] 3) The first product was mixed with carbon fiber and niobium metal carbide in a mass ratio of 1:0.005:0.01, added to anhydrous ethanol for ultrasonic stirring and dispersion, stirred and evaporated in a 90°C water bath to obtain a dry paste, the paste was dried at 120°C, and the dried product was ground. The ground product was sintered at 600°C in a nitrogen atmosphere for 10 h to obtain the positive electrode active material of this embodiment; according to ICP testing, the mass content of the doping element in the positive electrode active material was 2000pm.
[0128] Example 5
[0129] 1) dissolving nickel sulfate hexahydrate and manganese sulfate monohydrate in a certain molar ratio in deionized water to obtain a mixed salt solution, wherein the molar ratio of nickel to manganese is 35:65, the concentration of the mixed salt solution is 2.5 mol / L, and a 10 mol / L NaOH solution is prepared, and the two are added to a reactor at the same time under the protection of a nitrogen atmosphere, and the temperature of the reaction system is controlled at 60° C. After reaction, aging, washing, filtering, and drying, a hydroxide precursor Ni 0.35 Mn 0.65 (OH)2;
[0130] The hydroxide precursor is mixed evenly with Li2CO3 and TeO2 to obtain a mixed material, wherein the ratio of the molar amount of lithium element to the molar amount of metal element in the hydroxide precursor is 1.2:1, and the mass ratio of Te element to the hydroxide precursor is 0.005:1; the mixed material is placed in a box furnace into which air is passed, and sintered at 950°C for 10 hours to obtain a lithium-rich manganese-based positive electrode material;
[0131] 2) The above lithium-manganese-rich positive electrode material is mixed with La 0.9 Sr 0.1 AlO3 materials were mixed in a mass ratio of 1:0.001, added to deionized water to obtain a suspension, stirred evenly with a magnetic stirrer, and then spray-dried. The spray-dried product was sintered at 600° C. for 15 h to obtain a first product.
[0132] 3) The first product was mixed with carbon nanotubes and tungsten metal carbide in a mass ratio of 1:0.05:0.001, added to anhydrous ethanol for ultrasonic stirring and dispersion, stirred and evaporated in a 90°C water bath to obtain a dry paste, the paste was dried at 120°C, and the dried product was ground. The ground product was sintered at 450°C in a nitrogen atmosphere for 8 h to obtain the positive electrode active material of this embodiment; according to ICP testing, the mass content of the doping element in the positive electrode active material was 5000 pm.
[0133] Example 6
[0134] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass ratio of the hydroxide precursor to the Cr element is adjusted to 2000:1;
[0135] According to the ICP test, the mass content of the doping element in the positive electrode active material in this embodiment is 500 ppm.
[0136] Example 7
[0137] The preparation method of the positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 2), the mass ratio of the lithium-rich manganese positive electrode material to the LaAlO3 material is adjusted to 1:0.0005;
[0138] Then, the thickness of the first coating layer in the positive electrode active material in this embodiment is 2 nm, and the mass content of the first coating layer in the positive electrode active material is 0.05 wt %.
[0139] Example 8
[0140] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that, in step 3), the mass ratio of the first product to the carbon nanotubes and the tungsten metal carbide is adjusted to 1:0.06:0.0006;
[0141] The thickness of the second coating layer in the positive electrode active material in this embodiment is 12 nm, and the mass content of the second coating layer in the positive electrode active material is 6.06 wt %.
[0142] Example 9
[0143] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass ratio of the first product to the carbon nanotubes and tungsten metal carbide is adjusted to 1:0.003:0.03, wherein the mass ratio of the carbon nanotubes to WC is 0.1:1.
[0144] Example 10
[0145] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass ratio of the first product to the carbon nanotubes and tungsten metal carbide is adjusted to 1:0.0053:0.0001, wherein the mass ratio of the carbon nanotubes to WC is 53:1.
[0146] Embodiment 11
[0147] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 1), no Cr element is doped.
[0148] Example 12
[0149] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the carbon material also includes graphene, and the mass ratio of the first product to the carbon nanotubes, graphene and tungsten metal carbide is 1:0.0025:0.0025:0.001.
[0150] Example 13
[0151] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Example 1, except that in step 3), the carbon material also includes Ketjen black, and the mass ratio of the first product to the carbon nanotubes, Ketjen black and tungsten metal carbide is 1:0.0025:0.0025:0.001.
[0152] Comparative Example 1
[0153] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that the surface of the lithium-rich manganese-based positive electrode material is not coated with the first coating layer and the second coating layer.
[0154] Comparative Example 2
[0155] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that the positive electrode active material in this comparative example does not have a first coating layer. Specifically, in step 2), the lithium manganese-rich positive electrode material is added to deionized water to obtain a suspension, which is stirred evenly with a magnetic stirrer and then spray-dried. The spray-dried product is sintered at 800° C. for 10 h to obtain the first product, while the rest remains unchanged.
[0156] Comparative Example 3
[0157] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that the positive electrode active material in this comparative example does not have a second coating layer. Specifically, the positive electrode active material of this comparative example is directly obtained after step 2) without performing step 3).
[0158] Comparative Example 4
[0159] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 3), the first product and tungsten metal carbide are mixed in a mass ratio of 1:0.006, added to anhydrous ethanol for ultrasonic stirring and dispersion, and then kept consistent.
[0160] Comparative Example 5
[0161] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 3), the first product and carbon nanotubes are mixed at a mass ratio of 1:0.006, added to anhydrous ethanol for ultrasonic stirring and dispersion, and then kept consistent.
[0162] Comparative Example 6
[0163] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 3), the carbon nanotubes are replaced by glucose, and the mass ratio of the first product to glucose and WC is 1:0.005:0.001.
[0164] Test example
[0165] 1. The positive electrode active materials prepared in the above Example 1 and Comparative Example 1 were subjected to SEM test, and the positive electrode active materials prepared in Example 1 were subjected to TEM test and XRD test respectively. The test results are shown in FIG. Figure 1-Figure 4 .
[0166] Figure 1 is a SEM image of the positive electrode active material prepared in Example 1, Figure 2 is a SEM image of the positive electrode active material prepared in Comparative Example 1. Figure 1 and Figure 2 It can be seen that the positive electrode active material includes secondary particles formed by agglomeration of primary particles, and the surface of the positive electrode active material in Example 1 is obviously more coated than that in Comparative Example 1. Figure 1 In the figure, we can see some filament-like substances, which are carbon nanotubes in the second coating layer.
[0167] Figure 3 is a TEM image of the positive electrode active material prepared in Example 1, Figure 3 In the present invention, the surface of the lithium-rich positive electrode bulk phase (i.e., the lithium-rich manganese-based positive electrode material) is coated with a first coating layer, and the surface of the first coating layer is coated with a second coating layer, wherein the first coating layer is LaAlO3 material, and the second coating layer is a mixture of carbon nanotubes and tungsten metal carbide.
[0168] Figure 4 is the XRD pattern of the positive electrode active material prepared in Example 1. Figure 4 It can be seen that after the lithium-rich manganese-based positive electrode material is coated with the first coating layer and the second coating layer, its crystal structure changes.
[0169] 2. The physical and chemical properties of the positive electrode active materials prepared in the above examples and comparative examples were characterized. The characterization results are shown in Table 1.
[0170] Table 1
[0171]
[0172] 2. The positive electrode active materials prepared in the above-mentioned Examples 1 to 13 and Comparative Examples 1 to 6 are made into lithium-ion batteries, comprising the following steps:
[0173] The positive electrode active material prepared in the above examples and comparative examples was mixed with the conductive agent Super-P and polyvinylidene fluoride (PVDF) in a mass ratio of 90:5:5, added to N-methylpyrrolidone (NMP), and coated on a functional surface of an aluminum foil after stirring for a certain period of time. After vacuum drying at 120°C, it was cut into a pole piece with a diameter of 15 mm, and a compacted density of 2.8 g / cm 3 , surface density is 10g / cm 2 The positive electrode sheet is a lithium metal sheet as the negative electrode, and PP / PE / PP is used as a separator. The positive electrode sheet, the separator, and the negative electrode are stacked in sequence in a button cell, and the electrolyte is injected and sealed to obtain a CR2430 button cell. The electrolyte includes a lithium salt, a solvent, and an additive. The lithium salt is lithium hexafluorophosphate (LiPF6) with a concentration of 1 mol / L. The solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1. The additive is vinylene carbonate (VC) and fluoroethylene carbonate (FEC) in a volume ratio of 1:1.
[0174] The button cell prepared above was tested:
[0175] 1) First Coulombic efficiency
[0176] The button cell was tested for charge and discharge in the Blue Power Battery Test System. The test conditions were: 25°C, charge and discharge voltage window of 2.0-4.55V, 0.2C constant current charging to 4.55V, constant voltage charging to a cut-off current of 0.05C, and then discharged to 2.5V at 0.2C, where 1C = 230mAh / g, and the charge specific capacity, discharge specific capacity and first cycle coulombic efficiency were recorded.
[0177] 2) Rate performance
[0178] The button cell was tested for rate performance in the Blue Electric Battery Test System. The test conditions were: 25°C, charge and discharge voltage window of 2.5-4.55V, after one cycle of activation at 0.1C / 0.1C, 5 cycles of testing at 0.33C / 0.33C, and 5 cycles of testing at 1C / 1C, where 1C = 230mAh / g, and the discharge capacity of each cycle was recorded. The ratio of the discharge capacity at the last cycle of the 1C cycle to the discharge capacity at the last cycle of the 0.33C rate cycle was the battery rate performance.
[0179] 3) Cycle performance
[0180] The button cell was tested for cycle performance in a blue battery test system. The test conditions were: 25°C, charge and discharge voltage window of 2.5-4.55V, after one cycle of activation at 0.1C / 0.1C, 50 cycles were tested at 0.33C / 0.33C rate, and the discharge capacity of each cycle was recorded; the cycle capacity retention rate (%) = (discharge capacity of the first cycle at 0.33C rate / discharge capacity of the 50th cycle at 0.33C rate) × 100%.
[0181] The test results are shown in Table 2.
[0182] Table 2
[0183]
[0184]
[0185] From Table 1 and Table 2, we can see that:
[0186] Compared with Comparative Examples 1 to 6, the batteries in Examples 1 to 13 have higher first coulombic efficiency, rate performance and cycle performance. Among them, the first coulombic efficiency of the battery in Example 1 is as high as 85.1%, and the corresponding 1C / 0.33C rate performance is as high as 92.8%, and the cycle capacity retention rate is 94.5%, which is significantly higher than the performance of the batteries in Comparative Examples 1 to 6. It can be seen that the positive electrode active material in the present invention can effectively improve the first coulombic efficiency, rate performance and cycle performance of lithium-ion batteries.
[0187] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material includes secondary particles formed by agglomeration of primary particles, the secondary particles are provided with coating layers on their surfaces, and the coating layers include a first coating layer and a second coating layer; the first coating layer is provided on the surface of the secondary particles, and the second coating layer is provided on the surface of the first coating layer; The secondary particles include a lithium-rich manganese-based positive electrode material, the first coating layer includes a perovskite material, the second coating layer includes a carbon material and a metal carbide, and the carbon material includes a one-dimensional carbon material.
2. The positive electrode active material according to claim 1, characterized in that The chemical composition of the perovskite material is A x B 1-x CO3; Wherein, 0≤x≤1, A and B each independently include at least one of La, Ce, Ca, Sr, Ba, Mg, and Y, and C includes at least one of Al, Ni, Ti, Zr, Cr, Te, and Nb; Preferably, the perovskite material includes LaAlO3, La 0.9 Sr 0.1 AlO3, LaNiO3, La 0.9 Sr 0.1 NiO3, BaZrO3, MgTiO3, BaTiO3, SrTiO3, Ba 0.8 Sr 0.2 TiO3、Ba 0.7 Sr 0.3 TiO3、Ba 0.6 Sr 0.4 At least one of TiO3.
3. The positive electrode active material according to claim 1 or 2, characterized in that: The one-dimensional carbon material includes at least one of carbon nanotubes, carbon fibers, carbon nanowires, and carbon nanorods; And / or, the metal carbide includes at least one of niobium metal carbide, titanium metal carbide, molybdenum metal carbide, and tungsten metal carbide.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The thickness of the first coating layer is 3-7 nm, and / or the thickness of the second coating layer is 5-10 nm.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The mass percentage of the first coating layer in the positive electrode active material is 0.1-2.0 wt %, and / or the mass percentage of the second coating layer is 0.5-5.1 wt %.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that: The mass ratio of the carbon material to the metal carbide is (0.5-50):
1.
7. The positive electrode active material according to any one of claims 1 to 6, characterized in that: The positive electrode active material further includes a doping element, and the doping element includes at least one of Ti, Al, Cr, Ta, W, Te, and Nb; Preferably, the mass content of the doping element in the positive electrode active material is 1000 to 5000 ppm.
8. The positive electrode active material according to any one of claims 1 to 7, characterized in that: The carbon material also includes at least one of graphene, fullerene, Ketjen black, Super-P, and acetylene black.
9. The positive electrode active material according to claim 8, characterized in that The carbon material is graphene and / or Ketjen black.
10. A method for preparing a positive electrode active material according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) granulating the raw materials including the lithium-rich manganese-based positive electrode material and the perovskite material, and then performing a first sintering in an air atmosphere to obtain a first product; wherein the first sintering temperature is 600 to 800° C., and the holding time is 10 to 15 hours; 2) Mixing the raw materials including the first product, the carbon material and the metal carbide with a solvent, evaporating and then performing a second sintering in an inert atmosphere to obtain a positive electrode active material; wherein the second sintering temperature is 300 to 600° C. and the insulation time is 5 to 10 hours.
11. The method for preparing a positive electrode active material according to claim 10, characterized in that: Step 1) also includes mixing and sintering a lithium-rich manganese-based positive electrode material precursor with a lithium source and a compound containing a doping element, the sintering temperature is 800-1000° C., and the holding time is 10-20 hours to obtain the lithium-rich manganese-based positive electrode material; wherein the doping element in the compound containing the doping element includes at least one of Ti, Al, Cr, Ta, W, Te, and Nb; Preferably, the mass ratio of the doping element to the lithium-rich manganese-based positive electrode material precursor is (0.001-0.005):
1.
12. The method for preparing a positive electrode active material according to claim 10 or 11, characterized in that: The mass ratio of the lithium-rich manganese-based positive electrode material to the perovskite material is 1: (0.001-0.02); And / or, the mass ratio of the first product to the carbon material and the metal carbide is 1:(0.005-0.05):(0.001-0.01).
13. The method for preparing a positive electrode active material according to any one of claims 10 to 12, characterized in that: The solvent includes an anhydrous organic solvent; Preferably, the anhydrous organic solvent includes at least one of anhydrous ethanol, o-dichlorobenzene, and N-methylpyrrolidone.
14. A positive electrode sheet, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 9, or the positive electrode active material prepared by the preparation method according to any one of claims 10 to 13.
15. A lithium ion battery, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 9, or the positive electrode active material prepared by the preparation method according to any one of claims 10 to 13, or the positive electrode sheet according to claim 14.
Citation Information
Cited By
Preparation method of modified lithium cobalt oxide positive electrode material with high-temperature stability
CN120943305A
Preparation method of modified lithium cobalt oxide positive electrode material with high temperature stability
CN120943305B